Mutations within the P-Loop of Kir6.2 Modulate the Intraburst Kinetics of the Atp-Sensitive Potassium Channel - Proks, Peter (The Rockefeller University Press, 2001)
The ATP-sensitive potassium (K(ATP)) channel exhibits spontaneous bursts of rapid openings, which are separated by long closed intervals. Previous studies have shown that mutations at the internal mouth of the pore-forming (Kir6.2) subunit of this channel affect the burst duration and the long interburst closings, but do not alter the fast intraburst kinetics. In this study, we have investigated the nature of the intraburst kinetics by using recombinant Kir6.2/SUR1 K(ATP) channels heterologously expressed in Xenopus oocytes. Single-channel currents were studied in inside-out membrane patches. Mutations within the pore loop of Kir6.2 (V127T, G135F, and M137C) dramatically affected the mean open time (τ(o)) and the short closed time (τ(C1)) within a burst, and the number of openings per burst, but did not alter the burst duration, the interburst closed time, or the channel open probability. Thus, the V127T and M137C mutations produced longer τ(o), shorter τ(C1), and fewer openings per burst, whereas the G135F mutation had the opposite effect. All three mutations also reduced the single-channel conductance: from 70 pS for the wild-type channel to 62 pS (G135F), 50 pS (M137C), and 38 pS (V127T). These results are consistent with the idea that the K(ATP) channel possesses a gate that governs the intraburst kinetics, which lies close to the selectivity filter. This gate appears to be able to operate independently of that which regulates the long interburst closings.